Legal Protection of PPAT-Notary in Making A Deed Based on False Information of Parties - Euis Istianti (Sultan Agung Notary Law Review, 2021)
The focus of this research has the following objectives: (1) legal certainty over the deed and the notary's responsibility for false statements of the parties; (2) legal protection for PPAT notaries who make a deed of sale and purchase based on false information from the parties. (3) an example of the waiver of rights if it turns out that there are false statements from the parties in accordance with article 51 paragraph 2 of the Criminal Code. This study uses a normative juridical research method, with the collection of literature study data, and the theory used is Hans Khelsen's Theory of Legal Protection. The results of the study conclude: (1) A notary deed will not have legal certainty if the notary as a public official (openbaar ambtenaar) who is authorized to make an authentic deed does not make a deed in accordance with applicable regulations or is carried out against the law. (2) Legal protection for a PPAT notary who makes a deed of sale and purchase based on the parties' false information is only based on the right of denial and good faith of the notary himself, if the notary does not have good faith, then the right of refusal does not apply. (3) Waiver of rights if it turns out that there is false information from the parties in accordance with Article 51 paragraph 2 of the Criminal Code, if the notary participates in the false information, then the notary cannot be free from punishment. Suggestions put forward: (1) The Public Prosecutor should add the related article into a claim in Article 264 Paragraph (1) in conjunction with Article 55 Paragraph (1) and 56 Paragraph (1) and Paragraph (2) of the Criminal Code. And there should also be a claim against the party who ordered to do this forgery and use this fake deed so that justice is truly served. (2) The Notary should be able to refuse requests from the appearers that are not in accordance with the provisions of the legislation, this is also a form of prudence of a Notary in order to avoid legal problems that will harm later. (3) Notaries should have and have good intentions to account for their actions.